Relationship between Knowledge Level of Pregnant Women About Ante Natal Care (ANC) with Compliance with the Ante Natal Care (ANC) Schedule at the Nusawungu II Community Health Center in 2024 - Karningsih, Karningsih; Noviyana, Alfi (Pena Medika : Jurnal Kesehatan, 2024)
Survey Data Kesehatan Indonesia (SDKI) on 2017,  results show that the MMR is 305/100,000 live births. In Central Java, in 2022 it will be 41/100,000 live births in Cilacap district in 2023 11 Maternal Deaths Analyzing the relationship between pregnant women's knowledge about ANC and ANC schedule compliance. This research is quantitative. The research design used is a cross-sectional study. The population was TM III pregnant women in the Nusawungu 2 health center area. The research sample was 60 pregnant women with a gestational age of more than 36 week. Research analysis was carried out univariate and bivariate using Spearman rank. The Spearman's rank test obtained a p-value of 0.00 (< 0.05), which means that there is a relationship between the level of knowledge of pregnant women about ANC and compliance with the ANC schedule with a sufficient correlation coefficient (strength of relationship), namely 0.466. Pregnant women are expected to continue to increase their knowledge about pregnancy. Midwives should continue to improve their knowledge, and skills in assessing and providing care according to needs. The Nusawungu 2 health service and community health center should increase efforts to disseminate health information, process available data as basic data for policy making by involving cross-program roles and related cross-sectors.